Globalisation everywhere, except in the growth numbers: Pessimism reaffirmed? - Meissner, Christopher; Oosterlinck, Kim; Huberman, Michael (CEPR, 2015)
Understanding the relationship between trade and growth is still at the core of the economics profession. This column seeks to identify the pathways by which globalisation affects economic growth looking at the case of Belgium in the decades preceding the First World War. It argues that the collapse in fixed export costs promoted the entry of uncompetitive firms into export markets and as the trade component of GDP rose, the share of high performing firms contracted, slowing growth.

Technology and Geography in the Second Industrial Revolution: New Evidence from the Margins of Trade - Huberman, Michael; Meissner, Christopher M.; Oosterlinck, Kim (The Journal of Economic History, 2017)
Belle Époque Belgium recorded an unprecedented trade boom. Exploiting a new granular trade dataset, we find that the number of products delivered abroad and destinations serviced more than doubled in less than 40 years. To explain this remarkable achievement, we study the relationship between trade costs and the intensive and extensive margins of trade. The establishment of a foreign diplomatic network that lowered beachhead costs and enabled the entry of new products was an essential fact of the trade boom. Interestingly, the expansion in trade in certain sectors did not translate into faster productivity growth. We offer some explanations.